Oxford reading tree : level 3 : floppy's phonics : sounds and letters : . Book 18 - Hunt, Roderick; Hepplewhite, Debbie ([S.l.] : Oxford University Press, 2011)
There are 6 books at Level 3: Book 13 practises 'ai ee igh' Book 14 practises 'oa oo oo' Book 15 practises 'ar or ur' Book 16 practises 'ow oi ear' Book 17 practises 'air er er' Book 18 practises 'ue ue ure' Each sound is explored through an Oxford Reading Tree scene, first the children should say the sound and trace the letters in the panel, before looking at the key word and picture and saying the sound, there is a list of decodable words for them to read and then they can try to find all words they can that include the focus sound within the picture, some are labelled some are not! Consolidation activities include matching, tracing and reading. There are a total of 42 books in this series from Level 1 to Level 5 (Letters and Sounds Phase 1 to Phase 5)